Insignificant antidiabetic activity of rhizome of Zingiber zerumbet (Journal of Pharmaceutical Negative Results, 2010)
Objective: To investigate the antidiabetic activity of Z. zerumbet in streptozotocin (STZ)-induced diabetic rats. Materials and Methods: The diabetic rats were given aqueousextract of Z. zerumbet (200 mg/kg) and glibenclamide (10 mg/kg) for 21 days, and theirhypoglycemic activity and effect on body weight were assessed. Result: The treatmentwith aqueous extract of Z. zerumbet and glibenclamide both showed hypoglycemicactivity but efficacy of Z. zerumbet is not as significant as glibenclamide. Glibenclamidemaintain the body weight of rats throughout the study period, whereas the body weightof Z. zerumbet-treated rats significantly falls. Conclusion: This study suggests thataqueous extract of Z. zerumbet shows no significant activity in STZ-induced diabetic rats.